2008
DOI: 10.1016/j.numecd.2006.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The effects of polyphenols in olive leaves on platelet function

Abstract: Olive leaf polyphenols derived from O. europaea L. leaves inhibited in vitro platelet activation in healthy, non-smoking males. Further bioavailability studies need to be undertaken to determine the in vivo effect of extract on platelet function and to validate the present results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 24 publications
2
75
0
3
Order By: Relevance
“…Several studies have investigated the phenolic composition of olive leaves [12, 34-38, [58][59][60]. Pereira et al [32] found higher amounts of phenolic compounds in aqueous extracts of olive leaves than in extracts of mixtures of water and methanol of the same and other olive leaf cultivars.…”
Section: Polyphenolic Compounds In Olive Leavesmentioning
confidence: 99%
“…Several studies have investigated the phenolic composition of olive leaves [12, 34-38, [58][59][60]. Pereira et al [32] found higher amounts of phenolic compounds in aqueous extracts of olive leaves than in extracts of mixtures of water and methanol of the same and other olive leaf cultivars.…”
Section: Polyphenolic Compounds In Olive Leavesmentioning
confidence: 99%
“…17,28,29 Bu etkinin sebebi olarak fosfolipaz C aktivasyonu, araşidonik asit metabolizması ve hidrojen peroksidin seviyesinin azalması gösterilmektedir. 30 Zeytin yaprağında bulunan polifenollerin lipid profili üze-rine olumlu etkileri yapılan çalışmalarla desteklenmektedir.…”
Section: Zeyti̇n Yaprağinin Li̇pi̇d Profi̇li̇ üZeri̇ne Etki̇si̇unclassified
“…Çalışmanın sonunda zeytin yaprağı polifenollerinin muhtemelen araşi-donik asit metabolizması boyunca üretilen ve platelet agregasyonuna sebep olan H 2 O 2 'yi temizleyici özelliğinden dolayı platelet agregasyonunu önemli ölçüde inhibe ettiği gösterilmiştir. 30 Erkek wistar albino ratlar üzerinde yapılan bir başka çalışmada oral olarak 7 gün boyunca 1 mg/kg, 5mg/kg, 10mg/kg, 20mg/kg, 50 mg/kg ve 100mg/kg dozlarında hidroksitirozolün ratlarda tromboksan sentezini inhibe ederek ve nitrik oksit üretimini arttırarak platelet agregasyonunu engellediği gös-terilmiştir. 70 Yine yapılan bir başka çalışmada sikloolivil ve oleuropeinin platelet agregasyonunu azalttığı bildirilmiştir.…”
Section: Zeyti̇n Yaprağinin Anti̇tromboti̇k Etki̇si̇unclassified
“…The underlying mechanisms for theses effects include tromboxane reduction, decrease of ADP reactivity and ATP release from platelets, decrease of platelet-activating factor Karantonis et al, 2002;Karantonis et al, 2006;Perez-Jimenez et al, 2006;Singh et al, 2008;Sirtori et al, 1986;Smith et al, 2003). Effects of wine, a common element in certain countries consuming Mediterranean Diet have been also examined in some studies, but results are inconclusive.…”
Section: Mediterranean Diet and Hemostasismentioning
confidence: 99%